Activation of upper respiratory tract mucosal innate immune responses in cats by liposomal toll‐like receptor ligand complexes delivered topically. (15th February 2019) - Wheat, William; Chow, Lyndah; Coy, Jonathan; Contreras, Elena; Lappin, Michael; Dow, Steven
Abstract : Background: Nonspecific induction of local innate immune responses by mucosally administered immunotherapy is a new approach to protection from upper respiratory tract infections. Therefore, a new liposome‐toll‐like receptor complex (LTC) immune stimulant was developed and investigated for its ability to activate innate immune responses in cats, both in vitro and in vivo, as part of an initial evaluation of LTC for use as an immunotherapeutic agent in cats. Objectives: We hypothesized that LTC could activate innate immune responses in cats after topical application to nasal and oropharyngeal mucosal surfaces. Animals: Mucosal immune responses to topical administration of LTC were assessed in 7 healthy, purpose‐bred cats, and in vitro responses were assessed using blood samples from healthy cats. Methods: Cytokine and cellular immune responses to LTC were evaluated in blood samples, nasal lavage specimens, and pharyngeal swabs from cats, using reverse transcriptase polymerase chain reaction assays, ELISA assays, and flow cytometry. Results: Liposome‐TLR complexes rapidly activated leukocytes in vitro, including upregulation of costimulatory molecule expression and cytokine production. Topical administration of LTC in healthy cats triggered rapid recruitment of monocytes to the nasal and oropharyngeal mucosa. Conclusions and Clinical Importance: Liposome‐TLR complexes were found to effectively activate innate immune responses in cats after mucosal administration. These findings suggest that LTC have potential for use as a new mucosally administered immunotherapy for nonspecific protection from viral and bacterial respiratory tract infections.